Implementasi Hak Pekerja dalam Pembayaran Upah Selama Proses Pemutusan Hubungan Kerja pada Perusahaan Kelapa Sawit di Kabupaten Siak - Lia Rahmawani Dalimunthe; Indra Afrita; Robert Libra (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
In article 157A of Law Number 6 of 2023 that in the process of termination of employment, employers and permanent workers must carry out their respective obligations, employers can carry out suspension actions and still pay wages and other rights, but in reality employers rarely apply article 157A. The purpose of the research is to analyze the Implementation, Obstacles and Efforts on Workers' Rights in Wage Payment During the Termination of Employment Process at Palm Oil Company in Siak Regency. This type of research is Sociological legal research. In this research, three approaches are used, namely the legislative approach and the data source case approach using primary data and secondary data. The data collection technique used is primary data through interviews and questionnaires. The conclusion of this study is the legal protection of workers' rights during the termination of employment by the company through the settlement of industrial relations disputes in which there are various interpretations regarding the wage process. Article 157A of Law Number 6 of 2023 states that the responsibility of employers and workers remains valid until the industrial relations dispute settlement agency makes a decision. The implementation in the process of termination of employment is that workers are no longer allowed to work by the company but do not carry out suspension actions, but there are many companies that do not carry out things regulated by law. With the existence of multi-interpretation regulations on wages, the process provides uncertainty for workers, as well as in the interim decision submitted by the worker/plaintiff which is rejected by the judge which is clear that the worker can prove that the employer does not carry out his obligations as it should.